Paulo Freire's Critical Pedagogy Analysis Of Educational Transformation - Nugraha, Asep Eka; Wibowo, Deki; Hendrawan, Budi (PT. Hafasy Dwi Nawasena, 2024)
The purpose of this study described critically in several aspects of Paulo Freire's critical pedagogy and its contribution to educational transformation. This study uses a qualitative approach with the literature study method, namely the data collection method by understanding and studying the theory of various literature related to research. This research is based on critical interpretation. This illustrates several aspects of Paulo Freire's book, The Pedagogy of the Oppressed. In addition, several other related sources are also considered as a basis. This research is based on the concept of several key terms, to draw conclusions based on several important Freire messages. The results showed that, (1) Provides a background in critical thinking, the theoretical basis of Freire's critical pedagogy, and his life experience. Freire's critical thinking about the